Управління фізичною культурою і спортом в територіальних громадах України - Канцур, Інна Григорівна; Сергієнко, Юрій Петрович; Кондратюк, Альона Віталіївна; Салій, Маргарита Олександрівна (Український державний університет імені Михайла Драгоманова, 2024)
У статті досліджено сутність управління фізичною культурою і спортом в територіальних громадах України. Наголошено, що в умовах територіальних громад роль управління фізичною культурою і спортом набуває нового розміру, адже це не лише питання забезпечення доступу до спортивних заходів, але й формування інфраструктури, що стимулює активність населення. Розглянуто наукові думки щодо розуміння фізичної культури і спорту. Виокремлено, що сфера фізичної культури та спорту виступає індикатором якості життя окремої людини, соціальних груп і суспільства загалом. Стан її діяльності допомагає виявленню різновидів соціальної нерівності та деякою мірою може переборювати окремі види нерівності, покращувати тим самим якість життя значної кількості людей. У підсумку виділено, що управління фізичною культурою і спортом на територіальному рівні в Україні визначається важливістю та багатогранністю його впливу на суспільний розвиток. Створення сприятливого середовища для фізичної активності, розвиток спортивної інфраструктури та підтримка спортивних ініціатив сприяють збереженню та зміцненню здоров’я громадян, соціальній інтеграції та формуванню єдиного національного ідентитету.

The article examines the essence and necessity of managing physical culture and sports in the territorial communities of Ukraine. It is emphasized that in the conditions of territorial communities, the role of managing physical culture and sports takes on a new dimension. Scientific opinions on the understanding of physical culture and sports are considered. It was determined that the modern market socio-economic system of Ukraine contributes to the formation and development of key aspects of the market of physical culture and sports services. It is highlighted that the field of physical culture and sports serves as an indicator of the quality of life of an individual, social groups and society in general. The state of its activity helps to identify types of social inequality and to some extent can overcome certain types of inequality, thereby improving the quality of life of a significant number of people. It has been established that the management of physical culture and sports in the territorial communities of Ukraine is a key factor for the social, economic and cultural development of the country, covers various spheres of public life and has a great impact on the general state of society. It is noted that the important aspects of physical culture and sports management at the local level are: physical activity and sports are the basis of a healthy lifestyle; sport unites citizens of different age groups, social classes and cultures; sport is an effective tool for developing youth potential; developed sports infrastructure attracts tourists and contributes to the development of the service sector; sport develops discipline, dedication and team spirit; active participation in physical exercises and sports events contrib utes to the formation of civic culture, increases the level of patriotism and readiness for active participation in public life. It has been proven that the management of physical culture and sports in territorial communities is a strategically important task for ensuring the sustainable development of society, improving the quality of life of citizens, and preserving national health. The creation of a favorable environment for physic al activity, the development of sports infrastructure and the support of sports initiatives contribute to the preservation and strengthening of the health of citizens, social integration and the formation of a unified national identity.
Keywords: управління; фізична культура; спорт; територіальні громади України; management; physical culture; sports; territorial communities of Ukraine